2013
DOI: 10.1007/s10620-013-2980-7
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Approach to Patients with Suspected Lactose Malabsorption

Abstract: The LBT may serve as a diagnostic screening tool for lactose malabsorption. Symptomatic patients with negative LBT results should be referred for second-line testing with the LIQT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Lactose malabsorption may be due to many conditions, including: congenital lactose deficiency; lactase nonpersistence, in which lactase production declines over time, often begining at about age 2 years and secondary lactase deficiency, which results from injury to the small intestine. Secondary lactase deficiency has been found in various gastrointestinal conditions including coeliac disease, Crohn's disease, infectious enteritis, SIBO, irritable bowel syndrome, radiation enteritis, gastrointestinal surgery and short bowel syndrome …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lactose malabsorption may be due to many conditions, including: congenital lactose deficiency; lactase nonpersistence, in which lactase production declines over time, often begining at about age 2 years and secondary lactase deficiency, which results from injury to the small intestine. Secondary lactase deficiency has been found in various gastrointestinal conditions including coeliac disease, Crohn's disease, infectious enteritis, SIBO, irritable bowel syndrome, radiation enteritis, gastrointestinal surgery and short bowel syndrome …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this instance, the collection of breath samples was performed according to previous methodological recommendations to ensure end‐alveolar breath samples . We measured both H2 and CH4 levels, as it has been shown that false negative findings are observed in 16% of cases when CH4 is not measured …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have proposed a flow chart, but biochemical blood testing following lactose ingestion and glucose level measurement are rarely evaluated 6 , 31 . Here, we present a diagnostic algorithm for LI, considering biochemical blood test results, clinical symptoms, and genotyping of the SNPs C>T -13910 and G>A -22018 .…”
Section: Discussionmentioning
confidence: 99%